Impact of Transportation on Carbon Dioxide Emissions from Locally vs. Non-locally Sourced Food - Striebig, Bradley; Smitts, Eric; Morton, Samuel (Ital Publication, 2019)
The concentration of carbon dioxide in the atmosphere continues to rise, and the global food system is a significant contributor that often gets overlooked when it comes to solving the problem. In this study, emissions related to food transportation were studied to determine what impact getting local food instead of non-local food could have on the overall emissions of the food system. The dining service at the university utilizes local food to varying extents when it is in season, and a life cycle assessment (LCA) was done on lettuce, tomatoes, strawberries, and chicken to compare the emissions associated with the production of these foods. The transport-oriented GREET software was used for the LCA along with information from the sustainability coordinator at the university itself to get results. Given a lack of publicly available data regarding crop cultivation in certain areas of the U.S., some information had to be obtained from databases in Europe, but results suggest that produce coming from the west coast to the Virginia campus can have four to five times the emissions associated with production, and produce from Florida can have roughly twice as many emissions associated with production. There is a relatively low number of LCAs done in America to compare this data to, but it somewhat fits in with many European studies. Some LCAs do not factor in transportation processes, but my results suggest that any American studies should factor in transportation since it can contribute greatly to the overall footprint of products. The current available software for LCAs lacks consistency between programs, all having different strengths and weaknesses, and needs to be improved for quality results in the future.